Immunoglobulin GM Genes, Cytomegalovirus Immunoevasion, and the Risk of Glioma, Neuroblastoma, and Breast Cancer - Pandey, Janardan P. (Frontiers in Oncology, 2014)
Human cytomegalovirus (HCMV), a common herpes virus, has been reported to be a risk factor for many diseases, including malignant diseases such as glioma, neuroblastoma, and breast cancer. Some of the HCMV-associated diseases (e.g. glioma) are rare. The question arises: How could a common virus be associated with uncommon diseases? Interactions between a major gene complex of the human immune system and a viral immunoevasion strategy—a probable mechanism of their co-evolutionary adaptation—may shed light on this paradox. To ensure its survival, HCMV has evolved sophisticated immunoevasion strategies. One strategy involves encoding decoy Fcγ receptors (FcγR), which may enable the virus to evade host immunosurveillance by avoiding the Fcγ-mediated effector consequences of anti-HCMV IgG antibody binding. Immunoglobulin G1 proteins expressing GM (γ marker) alleles 3 and 17 have differential affinity to the HCMV TRL11/IRL11-encoded FcγR, and thus act as effect modifiers of HCMV-associated malignancies. The high affinity GM 3 allele has been shown to be a risk factor for neuroblastoma, glioma, and breast cancer. Additional studies involving other viral FcγRs as well as GM alleles expressed on other IgG subclasses are warranted.